1974
DOI: 10.1002/eji.1830040715
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin classes in the hen's egg: Their segregation in yolk and white

Abstract: Hen's egg yolk contains at least two antigen-binding subclasses of IgG, derived from the hen serum and transmitted t o the chick. IgM and IeA. absent in volkInstitute of Animal Physiology, Babraham, and in newly hatched chick serum, were detected in the white of unembrvonated Cambridge+

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
139
0
6

Year Published

1976
1976
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 261 publications
(152 citation statements)
references
References 5 publications
7
139
0
6
Order By: Relevance
“…Previous studies have shown the presence of three immunoglobulin classes in birds (IgA, IgM and IgY), but IgY is found in higher concentration (5 to 15mg/mL) than IgM (1 to 3mg/mL) and IgA (0.3 to 0.5mg/mL) in serum (ROSE et al, 1974;KOWALCZYK et al, 1985). As for mammals, the IgM is the predominant isotype produced in the avian primary humoral response while IgY is the predominant form in the secondary response (DAVISON et al, 2008).…”
Section: Structural and Functional Features Of Igymentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have shown the presence of three immunoglobulin classes in birds (IgA, IgM and IgY), but IgY is found in higher concentration (5 to 15mg/mL) than IgM (1 to 3mg/mL) and IgA (0.3 to 0.5mg/mL) in serum (ROSE et al, 1974;KOWALCZYK et al, 1985). As for mammals, the IgM is the predominant isotype produced in the avian primary humoral response while IgY is the predominant form in the secondary response (DAVISON et al, 2008).…”
Section: Structural and Functional Features Of Igymentioning
confidence: 93%
“…However, the concentration of IgY in egg yolk varies greatly between different bird species and even between chicken lines (CARLANDER, 2002). Yolk IgY concentrations were reported to be in the range of 7.9mg/ml to 20-25mg/ ml (ROSE et al, 1974;KOWALCZYK et al, 1985), depending on the analytical method used. About 100-200mg of total IgY can be extracted from a single egg with 2-10% being antigen specifi c (SCHADE et al, 1994;CARLANDER, 2002).…”
Section: Transport Of Igy From the Serum To Egg Yolkmentioning
confidence: 99%
“…Since that time, elegant empirical studies have further elucidated the mechanisms of antibody transmission and the subsequent utilization of antibodies by offspring (e.g. Brambell 1970;Solomon 1971a;Rose et al 1974;Kowalczyk et al 1985). However, the potential implications of maternal antibody transmission for evolutionary processes have been largely neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Yolk contains IgY (IgG-like) while IgA and IgM are deposited in the egg albumen (Rose et al, 1974;Kovacs-Nolan and Mine, 2012;Bedrani et al, 2013). IgY, if present, occurs in very low concentration in egg albumen (Rose and Orlans, 1981).…”
Section: The Egg Albumenmentioning
confidence: 99%